Cooperative Learning Model in Tilawati Al Quran to Cultivate Student Characters: Multi-Case Study - Umar Jaeni; Ismet Basuki; Moedjiarto Moedjiarto (Studies in Learning and Teaching, 2020)
Education needs a generation that understands and is aware of a superior character culture. This study aims to analyze 25 student characters' development process in cooperative learning in Al-Quran tilawati at Junior High School Al Muslim of Sidoarjo, Islamic Junior High School of 1 Surabaya, and Junior High School of 34 Surabaya. This research method uses qualitative research. This type of research uses a multi-case study from three school places. The sample of this research is the principal, the coordinator of the Al Quran teaching model, the teacher of Al Quran, the teacher of Al Quran learning model of the tilawati model and the students and by using research instruments, namely observation (observation), interview (interview), questionnaire (questionnaire), documentation and the combination of the four or triangulation. Based on the research conducted, it was found that the process of growing 25 characters in learning Al Quran with the tilawati model at Junior High School Al Muslim of Sidoarjo, Islamic Junior High School of 1 Surabaya, and Junior High School of 34 Surabaya gave good and strong results and obtained the growth of 25 character attitudes, namely respect for teachers, discipline, courageous and caring for others, orderly, compassionate, tolerant, love of Allah, spirit of learning to study, focus, spirit, patient, tolerant, obedient, togetherness, fond of reading, hard work, curiosity, caring, democracy, love of peace, neat in clothes, thorough, tawakkal, brave, independent, unyielding, and creative.